Need to take special care of non-responders to hepatitis B vaccination among health-care workers, students and chronic patients - Angela Bechini; Paolo Bonanni; Maddalena Grazzini; Diana Paolini; Giulio Arcangeli; Nicola Mucci; Costanza Bini; Emilia Tiscione; Beatrice Zanella; Sara Boccalini (Human Vaccines & Immunotherapeutics, 2021)
Both our research and that published by Sticchi et al. on immunological memory against hepatitis B virus (HBV) in health-care workers (HCWs) vaccinated as infants or adolescents confirm that in those testing negative after the primary course, one additional (fourth) booster dose is able to elicit an anti-HBs response in >85% subjects. The fifth and the sixth doses further contribute substantially to a high overall response rate. The rate of subjects showing an anamnestic response after the booster dose was almost six-fold higher in HCWs compared to chronic patients. Since universal vaccination in Italy resulted in a significant decrease in HBV infections, special attention and testing should be addressed to those affected by chronic diseases.